United airlines, INC: unprecedented challenge in the global aviation industry: U.S. aviation giant with a competitive EDGE an equity research report on United Airlines (UAL: NYSE) - Wang, Sofia (2021)
This equity research report will first be focusing on the North American Arline industry, focusing afterwards on the long-term impacted caused by the Global pandemic outbreak –Covid-19. A further analysis will then be conducted with regards do United Airlines Inc. (UAL:NYSE), applying the previous research to provide a fair valuation for the group, resulting in an sustained recommendation of whether an investor should consider invest in UAL, or not. With the global pandemic crisis affecting every sector worldwide, the Aviation industry was the one that registered the most severe impact, having most of its fleet grounded since the end of the 1st quarter of 2020. Nonetheless, United was still able to diminish this impact by shifting towards Cargo and maintaining a suitable level of liquidity.